Aortic Stiffness is Associated with Increased Risk of Incident Dementia in Older Adults. - Cui, Chendi; Sekikawa, Akira; Kuller, Lewis H; Lopez, Oscar L; Newman, Anne B; Kuipers, Allison L; Mackey, Rachel H (J Alzheimers Dis, 2018)
Cardiovascular disease risk factors, including age, hypertension, and diabetes, contribute to aortic stiffness and subclinical cardiovascular and brain disease, increasing dementia risk. Aortic stiffness, measured by carotid-femoral pulse wave velocity (cfPWV), reduces the buffering of pulsatile blood flow, exposing cerebral small arteries to microvascular damage. High cfPWV is related to white matter hyperintensities and brain amyloid deposition, and to cognitive decline, but it is unclear whether cfPWV independently predicts incident dementia. Therefore, we tested the hypothesis that cfPWV predicts incident dementia in older adults, independent of potential confounders. The Cardiovascular Health Study Cognition Study followed 532 non-demented older adults with annual cognitive exams from 1998-99 through 2013. CfPWV was measured on 356 (mean age = 78, 59% women) between 1996-2000. Over 15 years, 212 (59.6%) developed dementia (median time from cfPWV measurement = 4 years). In age and sex-adjusted Cox models, cfPWV was significantly associated with increased risk of dementia, but systolic blood pressure, mean arterial pressure and pulse pressure were not. CfPWV (transformed as - 1/cfPWV) remained significantly associated with dementia risk when further adjusted for education, race, APOEɛ4, diabetes, body mass index, mean arterial pressure, and anti-hypertensive medication (hazard ratio = 1.60, 95% CI = 1.02, 2.51). Results were similar when further adjusted for baseline global cognition, subclinical brain measures, and coronary artery calcification. Finally, higher cfPWV was related to lower physical activity intensity and higher systolic blood pressure, heart rate, and waist circumference measured 5 years prior. An important unanswered question is whether interventions to slow arterial stiffening can reduce the risk of dementia.

Associations of body composition with incident dementia in older adults: Cardiovascular Health Study-Cognition Study. - Cui, Chendi; Mackey, Rachel H; Shaaban, C Elizabeth; Kuller, Lewis H; Lopez, Oscar L; Sekikawa, Akira (Alzheimers Dement, 2020)
INTRODUCTION: A body of literature reported associations between late-life general adiposity measures (eg, body mass index) and dementia. Little is known about the association of late-life body composition with dementia risk. METHODS: We determined this association among cognitively normal participants from the Cardiovascular Health Study- Cognition Study. Body composition was assessed by dual-energy x-ray absorptiometry in 1994-1995. Dementia was ascertained at annual follow-up from 1998-1999 to 2013. Associations of body composition with incident dementia were assessed by the Fine-Gray model. RESULT: Among 344 participants (mean age 78, 62.2% women), body composition was significantly different between men and women, despite similar body mass indexes (BMIs). Increased dementia risk was significantly associated with lower lean mass in men and marginally with low appendicular lean mass in women. DISCUSSION: Decreased lean mass was an indicator of increased dementia risk in older adults. Studies should test whether preventing lean mass loss in older adults reduces dementia risk.